Kritik Ibn al-Jauzi Terhadap Hadis dalam Kitab Ihya Ulum ad-Din dan Pembelaan Abu al-Fadl al-Iraqi - A’an Mujibur Rohman (Jalsah : The Journal of Al-quran and As-sunnah Studies, 2021)
In the world of Islamic intellectuals, Al-Ghazali is one of the Sufistic figures who understands Islam very well. Arguments and ways of thinking about philosophy, monotheism and others were able to become a bridge for Muslims in that era. But apart from the intellectual prowess of al-Ghazali can not be separated from the criticism of his thinking. Some scholars at that time tried to criticize al-Ghazali's thoughts, especially about the hadith arguments that he used in Islamic law. Some scholars' considered that al-Ghazali used the hadith maudlu'. This is as seen in one of his monumental works, Ihya 'Ulum ad-Din, both for the purpose of at-targhib (providing motivation) and at-tarhib (scaring), and/or fadhail al-a'mal (the virtue of attitude/ behavior). It is interesting to briefly examine the epistemological framework of hadith in al-Ghazali's thought, which according to some scholars' has a tasahhul (loose) attitude in terms of hadith transmission, thus drawing criticism from some scholars and even orientalists, and the basis held by al-Ghazali in narrating and using hadiths that are af and even willing' quality, especially those related to haram and halal. However, this monumental book by al-Ghazali is considered a very great book in its era until now because it includes various types of knowledge.